An Ontology Construction Method for Educational Domain - Zhong Luo; Ma Deng; Liu Yongjian; Yuan Jingling (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
Ontology is regarded as an effective method of knowledge modeling and has been hot researched in knowledge engineering. This paper puts it into the design of educational resource system, taking Seven-step Methodology construction as the basis, adopting the software engineering structured design methodology, proposes a general educational domain ontology construction method, and has made detailed descriptions for each step and deep analysis on the relationships between subject knowledge in university majors. Finally, for application, an undergraduate software engineering major domain ontology is designed by this method. The method has strong universality and portability, can be used as a reference for other domain ontology construction.